Kamienice opatów jędrzejowskich w Krakowie w XVIII wieku .......... 189 - Dettloff, Paweł (Dzieje i kultura Cystersów w Polsce, 2025)
THE TENEMENTS OF THE ABBOTS OF JEDRZEJOW IN CRACOW IN THE 18TH CENTURYIn the eighteenth century, the Cistercian abbey of Jędrzejów owned two tenement houses in Kraków on St. John Street, now numbered: 9 (in 1742-1758) and 20 (in 1732-1787). Both buildings were transformed on the commission of the abbey. To this day they remain distinctive for their late Baroque architectural form. They are a testimony to the capabilities and importance of the Jedrzejów abbey at that time. Owning such houses in a town was proof of wealth, and at the same time, it could become a source of income. Both buildings were rented. One of them, the largest (no. 20) was rebuilt into a representative palace. Initially, it served as a municipal residence of the abbots of Jędrzejów. The article presents in detail the historical data, functions and connections of both houses with the Cistercians in the eighteenth century.